1994
DOI: 10.1093/nar/22.15.3045
|View full text |Cite
|
Sign up to set email alerts
|

The human Y4 small cytoplasmic RNA gene is controlled by upstream elements and resides on chromosome 7 with all other hY scRNA genes

Abstract: Ro ribonucleoproteins (RNP) constitute a class of evolutionarily conserved small cytoplasmic (sc) RNPs whose functions are unknown. In human cells four distinctive scRNAs designated hY1, hY3, hY4 and hY5 are synthesized by RNA polymerase III (pol III) and accumulate as components of Ro scRNPs. The previously isolated hY1 and hY3 genes contain upstream sequences similar to the class III promoters for U6 and 7SK snRNAs. Additional mammalian Y scRNA genes have been refractory to cloning due to interference from n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
2

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 42 publications
1
25
0
2
Order By: Relevance
“…However, La was detected at these genes, along with pol III. Brf1 was not found, consistent with the prediction, based on sequence, that these genes have type III promoters (41,42). We have also tested 5S rRNA and tRNA Leu genes and again saw no association of Ro, although La is clearly detected (Fig.…”
Section: The Human Autoantigen Ro Is Not Found Associated With Pol Iii-supporting
confidence: 86%
“…However, La was detected at these genes, along with pol III. Brf1 was not found, consistent with the prediction, based on sequence, that these genes have type III promoters (41,42). We have also tested 5S rRNA and tRNA Leu genes and again saw no association of Ro, although La is clearly detected (Fig.…”
Section: The Human Autoantigen Ro Is Not Found Associated With Pol Iii-supporting
confidence: 86%
“…A corresponding increase in hdm2 transcript levels was seen in the nuclear pellets (P) after U0126 exposure. Semiquantitative PCR detection of the small cytoplasmic RNA scRNA hY4 (45) confirmed that the cell lysis technique efficiently separated cytoplasmic RNA from the nuclear pellet, whereas gapdh mRNA was present in both fractions. After U0126 treatment, hdm2 mRNA clearly becomes associated with the insoluble pellet.…”
Section: Pharmacological Inhibition Of Mek Activity Suppresses Hdm2 Pmentioning
confidence: 74%
“…In human cells, four Y RNAs (hY1, hY3, hY4, and hY5 RNA) are transcribed by RNA polymerase III from single copy genes, clustered into a single locus on chromosome 7 (Hendrick et al 1981;Maraia et al 1994Maraia et al , 1996Matera et al 1995). Y RNAs are not modified and fold into characteristic stem-loop structures ( Fig.…”
Section: Introductionmentioning
confidence: 99%